Guillain-Barré syndrome complicating pregnancy: a tragic dual loss - N., Sunanda; Vaidya, Shreya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Guillain-Barré syndrome (GBS) is a rare, immune-mediated neuropathy characterized by acute, progressive weakness and areflexia. Although its incidence in pregnancy parallels that of the general population, the third trimester and early postpartum period are particularly vulnerable due to immunological alterations. We report the case of a 24-year-old multigravida at 33 weeks gestation who presented with progressive quadriparesis and respiratory distress. Neurological evaluation revealed flaccid limb weakness with preserved sensation, and cerebrospinal fluid analysis demonstrated albuminocytological dissociation. Nerve conduction studies confirmed the acute motor axonal neuropathy (AMAN) variant of GBS. Despite timely administration of intravenous immunoglobulin, ventilatory support, and comprehensive multidisciplinary management, the patient experienced rapid deterioration, leading to maternal and fetal demise. This case underscores the aggressive nature and poor prognosis associated with the AMAN variant of GBS in pregnancy. Prompt recognition of neurological symptoms, early initiation of immunotherapy, and meticulous respiratory monitoring are critical for optimizing maternal and fetal outcomes. Awareness among clinicians regarding this rare but potentially fatal association is essential to facilitate early diagnosis and improve survival.